2014
DOI: 10.5267/j.msl.2013.12.031
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of circle of security on attachment and well-being in preschool children

Abstract: The purpose of this study was to determine the efficacy of Circle of Security (COS) on preschool children's attachment and well-being. 48 mothers with children's age 4 to 6 year were randomly selected through cluster sampling and randomly assigned to experimental and control groups (24 mothers and child in each group). Then the experimental group received 20 weekly COS sessions in the center of preschool. The attachment Q-set and Preschool children wellbeing questionnaire (PCWQ) were used as the pretest, post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, the core components in COS-VF are similar to the content of the original 20-week, group-based COS protocol that has shown promising results in quasi-experimental studies (see e.g., [16][17][18]), with the more recent addition of a small randomized trial that demonstrated its effectiveness on preschool children's attachment and well-being [19]. The main differences between the intervention protocols are its group-based format and focus on caregivers' core sensitivities, whereas COS-VF therapists work with individual families, focusing on strategies used to navigate close relationships and protect caregivers from emotional distress.…”
Section: Circle Of Security Virginia-family Modelmentioning
confidence: 99%
“…However, the core components in COS-VF are similar to the content of the original 20-week, group-based COS protocol that has shown promising results in quasi-experimental studies (see e.g., [16][17][18]), with the more recent addition of a small randomized trial that demonstrated its effectiveness on preschool children's attachment and well-being [19]. The main differences between the intervention protocols are its group-based format and focus on caregivers' core sensitivities, whereas COS-VF therapists work with individual families, focusing on strategies used to navigate close relationships and protect caregivers from emotional distress.…”
Section: Circle Of Security Virginia-family Modelmentioning
confidence: 99%
“…COS-I has shown positive results in uncontrolled trials on both improving the attachment of infants [ 29 , 30 ], toddlers and preschoolers [ 31 ] with a significant change in attachment from insecure to secure. A controlled Iranian trial of children age 4–6 years found significant improvements after the COS-I intervention on both the child’s attachment and child well-being after the intervention and in a 3 month follow-up, when compared with a control group [ 32 ]. This despite the small sample size (n = 48).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is no published research on COS-VF to date. However, the core components in COS-VF are similar to the content of the original 20-week, group-based COS protocol that has shown promising results in quasi-experimental studies (see, eg, [ 16 - 18 ]), with the more recent addition of a small randomized trial that demonstrated its effectiveness on preschool children’s attachment and well-being [ 19 ]. The main differences between the intervention protocols are its group-based format and focus on caregivers’ core sensitivities, whereas COS-VF therapists work with individual families, focusing on strategies used to navigate close relationships and protect caregivers from emotional distress.…”
Section: Introductionmentioning
confidence: 99%